Improvement of Methodology for Manual Energy Intake Estimation From Passive Capture Devices - Pan, Zhaoxing; Forjan, Dan; Marden, Tyson; Padia, Jonathan; Ghosh, Tonmoy; Hossain, Delwar; Thomas, J. Graham; McCrory, Megan A.; Sazonov, Edward; Higgins, Janine A. (Frontiers in Nutrition, 2022)
Objective: To describe best practices for manual nutritional analyses of data from passive capture wearable devices in free-living conditions. Method: 18 participants (10 female) with a mean age of 45 ± 10 y and mean BMI of 34.2 ± 4.6 kg/m2 consumed usual diet for three days in a free-living environment while wearing an automated passive capture device. Data from the first nine participants were used by three trained nutritionists to identify sources contributing to inter-nutritionist variance in nutritional analyses. The nutritionists implemented best practices to mitigate these sources of variance in the next nine participants. The three best practices to reduce variance in analysis of energy intake (EI) estimation were: 1) a priori standardized food selection, 2) standardized nutrient database selection, and 3) increased number of images captured around eating episodes. Results: Inter-rater repeatability for EI, using intraclass correlation coefficient (ICC), improved by 0.39 from pre-best practices to post-best practices (0.14 vs 0.85, 95% CI, respectively), Bland-Altman analysis indicated strongly improved agreement between nutritionists for limits of agreement (LOA) post-best practices. Conclusion: Significant improvement of ICC and LOA for estimation of EI following implementation of best practices demonstrates that these practices improve the reproducibility of dietary analysis from passive capture device images in free-living environments.